Agromorphological and Physicochemical Characteristics of F8 Rice Lines Derived from IR64 × Nagdong Cross - Evita Nuril Aisiyah; Muhammad Irfandi Burhanuddin; Elvina Azaria Fatimah; Angger Aisyah Hadiahning Gusti; Mohammad Ubaidillah (Jurnal Ilmu Pertanian Indonesia, 2026)
The amylose content of rice influences its taste and texture. Large-scale imports suit the community's demand for low-amylose rice. The Faculty of Agriculture at the University of Jember has a Japonica plant breeding line that crosses local rice types, specifically IR64, to generate stable progeny. However, it lacks several agromorphological and physicochemical investigations. Agromorphological characteristics include plant height, number of tillers, number of seeds per panicle, weight of 100 grains, and The Agrotechnology Laboratory at the University of Jember conducted physicochemical tests on amylose concentration, swelling power, gel consistency, and gelatinization temperature. The findings revealed that all observation variables were significantly different, except for plant height and gel consistency. The plant's height was the same as its parent, semi-dwarf; the number of tillers was medium to good; the number of seeds per panicle was 103−108; and the weight of 100 grains was 2.877−3.265 g. Each strain had a low amylose content ranging from 13.87% to 15.85%, a swelling power of 6.61% to 8.93%, a soft gel consistency, and a gelatinization temperature of less than 60°C. Keywords: agromorphology, amylose, physicochemical, IR64